G45 Parental fever knowledge: A randomised controlled trial to assess the effectiveness of an educational intervention to increase parental knowledge. (24th May 2017) - Kelly, M; McCarthy, S; O'Sullivan, R; Shiely, F; McGillicuddy, A; Dahly, D; Sahm, LJ
Abstract : Aims: Despite the existence of guidelines from national organisations, parental knowledge of fever and management of fever in children is incomplete. The aim of this study was to assess the effectiveness of an educational intervention to increase parental knowledge of fever. Methods: A prospective, multi-centre, randomised, two-parallel arm, controlled trial with blinded outcome ascertainment was conducted. A convenience sample of parents presenting at purposively selected GP practices, urgent and emergency care treatment centres and pharmacies in Cork, Ireland were invited to participate. An information leaflet for use in the trial was designed based on two previous studies with parents. Parents in the control arm were asked to complete a short questionnaire at randomisation (time-point 1) and again two weeks after randomisation (time-point 2). Parents in the intervention arm were asked to read an information leaflet on fever and management of fever in children, complete a short questionnaire at randomisation (timepoint 1) and again two weeks after randomisation (time-point 2). Results: A total of 100 parents participated at time-point 1 of the study, with 50 participants in each arm. After time-point 2, 39 parents from the control group and 34 parents from the intervention group had been successfully contacted. A greater proportion of the intervention group (76%) than the control group (28%) selected the correct temperature to recognise fever (38OC) at time-point 1. At time-point 2, 82.4% of the intervention group and 30.8% of the control group selected the correct temperature. When answers from the intervention and control groups were compared at both time points using simple logistic regression, participants in the intervention group were more likely to give the correct answer at both time points (initial questionnaire OR 8.143 CI 95% 3.325–19.943; after two weeks OR 10.5, CI 95% 3.448–31.972). Management practices were also positively influenced by the information leaflet (reduction in alternating between antipyretics and use of tepid sponging). Conclusions: An educational intervention can improve parental knowledge of fever and correct management strategies. The effect of the intervention was sustained over-time. This study highlights the need for public health authorities to consider incorporating this leaflet into resources for parents.